Aspek Psikologis pada Layanan Keperawatan Pasien Kanker Payudara: A Systematic Review - Yulia Indah Permata Sari; Waluyo Waluyo; Tria Anisa Firmanti; Sholihin Sholihin; Roby Aji Permana (Jurnal Penelitian Kesehatan SUARA FORIKES, 2020)
Background: Breast Cancer can be a traumatic and stressful experience for women but there are wide-ranging differences in the ways in which women respond and adapt to breast cancer. Purpose: to examines which sociodemographic, disease-related, and psychosocial factors predict psychological adaptation to breast cancer. Method: The database used to identify suitable articles obtained from Scopus, Pubmed, CINAHL and Science Direct was limited from 2011-2019, English, and fulltext articles. The literature review used the keywords “psychological, adaptation, breast cancer”. In searching articles used “AND”. Results: 31 articles met the inclusion criteria. Consistent sociodemographic and disease-related variables predictors of adaptation were income, fatigue, cancer stage, and physical functioning. Psychosocial factors, particularly optimism and trait-anxiety, as well as perceived social support, coping strategies, and initial levels of psychological functioning were found to be predictive of later depressive and anxiety symptoms, psychological distress and quality of life for women with breast cancer, in predictable ways. Conclusion: The majority of studies showed a significant relationship between psychosocial factors and psychological adaptation. These results pount to specific sociodemographic, disease-related, and psychosocial factors that can help to identify women at the time of diagnosis who are at risk for long-term psychological challenges so they can be reffered for psychological support that targets their specific needs and can improve their quality of life and mood, and decrease indicators of anxiety, depression and psychological distress. Keywords: psychological; adaptation; breast cancer ABSTRAK Latar Belakang: Kanker payudara dapat menjadi pengalaman yang traumatis dan juga menimbulkan stress bagi wanita, tetapi ada banyak perbedaan cara wanita merespons dan beradaptasi dengan kanker payudara. Tujuan: Untuk menguji faktor-faktor sosiodemografi, hal-hal terkait penyakit, dan faktor psikososial yang memprediksi adaptasi psikologis terhadap kanker payudara. Metode: Database digunakan untuk mengidentifikasi artikel yang sesuai diperoleh dari Scopus, PubMed, CINAHL, dan Science Direct terbatas untuk tahun 2011 hingga 2019, bahasa Inggris dan teks lengkap. Tinjauan literatur menggunakan kata kunci “psikologis, adaptasi, kanker payudara”. Dalam pencarian artikel menggunakan “AND”. Hasil: 31 artikel memenuhi kriteria inklusi. Variabel-variabel sosiodemografi dan hal-hal terkait penyakit yang menjadi prediktor adaptasi adalah pendapatan, kelelahan, stadium kanker dan fungsi fisik. Faktor-faktor psikososial, terutama optimisme dan kecemasan, serta dukungan sosial yang dirasakan, strategi koping, dan tingkat awal fungsi psikologis ditemukan menjadi prediksi gejala depresi dan kecemasan, tekanan psikologis dan kualitas hidup untuk wanita dengan kanker payudara. Kesimpulan: Sebagian besar penelitian menunjukkan hubungan yang signifikan antara faktor psikososial dan adaptasi psikologis. Hasil ini sesuai dengan faktor-faktor sosiodemografi, hal-hal terkait penyakit dan faktor psikososial dapat membantu mengidentifikasi wanita pada saat diagnosis yang berisiko terhadap tantangan psikologis jangka panjang sehingga mereka mendapatkan dukungan psikologis yang dapat meningkatkan kualitas hidup dan suasana hati mereka, dan mengurangi indikator kecemasan, depresi dan tekanan psikologis. Kata kunci: psikologis; adaptasi; kanker payudara